CRIMINAL-LEGAL DESCRIPTION OF CRIMES RELATED TO EXTREMISM - Nurumbetova Sadokat Allarovna (Scholar Express Journals, 2024)
In this article, the subjects of this crime are: 1) materials mixed with the ideas of religious extremism; 2) materials based on the ideas of religious separatism; 3) materials based on the ideas of religious fanaticism (fundamentalism); 4) materials aimed at extermination; 5) materials aimed at inciting to evict citizens by force; 6) materials intended to cause panic among the population
Keywords: The object of the crime; Religious extremism